Identifikasi Galur dan Gen-gen Terkait Toleran Kekeringan pada Padi Transgenik cv. T309 yang Mengandung Vektor Penanda Aktivasi - Tri Joko Santoso; Aniversari Apriana; Atmitri Sisharmini; Kurniawan R. Trijatmiko (Jurnal AgroBiogen, 2013)
Activation tagging is an efficient tool forfunctional analysis of the rice genes. We have developed anumber of transgenic rice lines (Oryza sativa L. ssp.japonica cv. Taipei 309) containing activation tagging vector.However, the phenotypes and genotypes of these lines, inrelation to the drought stress, have not been analyzed. Theobjectives of this research were to identify transgenic ricelines that showed tolerance to the drought stress and toidentify the genes that may be associated with the droughtstress. The drought stress tolerance in transgenic rice lineswas identified by testing their tolerance to the drought stressand also by detecting the presence of bar and nptII genes.The result showed that 56 out of 59 rice lines were resistantto Basta herbicide and three of them showed tolerance todrought stress, namely PA.T-1.2, PA.T-4.1, and PA.T-5.1 lines.PCR analysis showed that PA.T-1.2 and PA.T-4.1 containedboth hptII and bar genes, while the PA.T-5.1 line containedbar gene only. Thermal Asymetric Interlaced-PCR (TAILPCR)analysis showed that two genes may be asssociatedwith the drought stress tolerance. Those genes areOSJNBa0004120.14 that produces uridylate putative kinaseand OsPPCK2L that produces phosphoenolpyruvatecarboxylase kinase.